2019
DOI: 10.4049/jimmunol.1800898
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: IL-27 Attenuates Autoimmune Neuroinflammation via Regulatory T Cell/Lag3–Dependent but IL-10–Independent Mechanisms In Vivo

Abstract: IL-27 regulates immune responses in inflammation. The underlying mechanism of IL-27 functions has long been attributed to its ability to induce IL-10 production in activated CD4 T cells. In this study, we report that Foxp3+ regulatory T cells (Tregs) are the main target cells of IL-27, mediating its immunoregulatory functions in vivo. Systemically delivered IL-27 efficiently prevents the development of experimental autoimmune encephalomyelitis, an autoimmune inflammation in the CNS. However, it failed to do so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 18 publications
1
38
0
1
Order By: Relevance
“…In myelin oligodendrocyte glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis (EAE) model, Kadowaki et al 88 demonstrated that LAG-3 blockade abrogated the anti-inflammatory effect of gut environment-induced intraepithelial MOG-specific CD4 + T cells. Kim et al 89 also reported that the ability of in vitro-generated induced T reg (iT reg ) cells to rescue T reg -depleted mice from lethal EAE was dependent on the expression of LAG-3 on the iT reg cells.…”
Section: Lag-3 In Autoimmunitymentioning
confidence: 99%
“…In myelin oligodendrocyte glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis (EAE) model, Kadowaki et al 88 demonstrated that LAG-3 blockade abrogated the anti-inflammatory effect of gut environment-induced intraepithelial MOG-specific CD4 + T cells. Kim et al 89 also reported that the ability of in vitro-generated induced T reg (iT reg ) cells to rescue T reg -depleted mice from lethal EAE was dependent on the expression of LAG-3 on the iT reg cells.…”
Section: Lag-3 In Autoimmunitymentioning
confidence: 99%
“…In support, we recently demonstrated that IL-27 signaling in Tregs is indispensable in mediating Treg function to suppress chronic inflammation, because systemic IL-27 administration was unable to reverse autoimmune and allergic inflammation in the absence of Tregs or Treg expression of the IL-27R (27,28). IL-27 is known to antagonize iTreg differentiation if added to naive CD4 T cell activation (23).…”
Section: Discussionmentioning
confidence: 87%
“…In the context of GvHD, the level of endogenous IL-27 is elevated in recipient serum, which in turn inhibits Treg reconstitution and facilitates GvHD development (25). IL-27 plays a key role in regulating Foxp3 + Treg functions in chronic inflammation including colitis, allergic airway inflammation, autoimmunity, and cancers (24,(26)(27)(28)(29). These results suggest that IL-27mediated regulation of Treg functions may be a tool to mediate inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines made in the gastric mucosa during inflammation likely contribute to the development of preneoplastic changes such as atrophy, hyperplasia, metaplasia, and dysplasia that predispose to carcinogenesis. IL27 plays a protective role in other inflammatory diseases, 20 , 33 and recently was detected at high levels in human patients with chronic gastritis. 24 We hypothesized that IL27 also may play a protective role during gastritis.…”
Section: Resultsmentioning
confidence: 99%
“…The rIL27 dose was based on previous studies that successfully had prevented other inflammatory diseases using mini osmotic pumps loaded with rIL27. 20 , 33 Mice were killed 4 weeks after implantation and the severity of gastritis pathology and metaplasia development was assessed using the pathologic and immunofluorescent methods described previously. The stomachs of rIL27-treated mice were much healthier than those from untreated mice.…”
Section: Resultsmentioning
confidence: 99%